Analisis Perbandingan Penggunaan Pegas CVT Racing 1000 RPM 1500 RPM 2000 RPM terhadap Performa Sepeda Motor Honda Beat 110 CC - Muhammad Shobirin; Hermanu Kusbandono (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
In the era of automatic transmission or automatic transmission motorbikes, many people enjoy doing it in various circles compared to manual transmission motorbikes, these automatic transmission motorbikes are indeed fuel efficient and agile, but automatic motorbike users are not satisfied with their less optimal power, seeing the problems in The use of springs is a factor that influences the performance of automatic transmissions. The purpose of this study is to analyze one of the components of the Continuously Variable Transmission, namely the CVT spring. then compare the power and torque values to find out the comparison of the use of the three springs on the vehicle and retrieve data through the dynotest process. Tests using this dynotest tool produce the values of power, torque, and engine speed produced by the vehicle, this test uses three springs with different constant values such as 1000 Rpm, 1500 Rpm, 2000 Rpm to retrieve table and graphic data values and then compare the data to be converted into thrust and vehicle speed values. To obtain the maximum speed of the vehicle. From the experimental results, each spring produces a different transmission ratio. This results in the value of power and torque, which is produced by each different spring.